Amplification of lmbB1 gene in Streptomyces lincolnensis improves quantity and quality of lincomycin A fermentation. Issue 6 (2nd July 2020) - Yang, Jing; Ye, Ruifang; Zhang, Hongzhou; Liu, Yan
Abstract: As a lincosamide antibiotic, lincomycin is still important for treating diseases caused by Gram-positive bacteria. Manufacturing of lincomycin needs efforts to, e.g. maximize desirable species and minimizing unwanted fermentation byproducts. Analysis of the lincomycin biosynthetic gene cluster of Streptomyces lincolnensis, lmbB1, was shown to catalyze the conversion of L-dopa but not of L-tyrosine and then further generated the precursor of lincomycin A. Based on the principle of directed breeding, a strain termed as S. lincolnensis 24-2, was obtained in this work. By overexpressing the lmbB1 gene, this strain produces efficacious lincomycin A and suppresses melanin generation, whereas contains unwanted lincomycin B. The good fermentation performance of the mutant-lmbB1 ( M-lmbB1 ) was also confirmed in a 15 L-scale bioreactor, which increased the lincomycin A production by 37.6% compared with control of 6435 u/mL and reduced the accumulation of melanin by 29.9% and lincomycin B by 73.4%. This work demonstrated that the amplification of lmbB1 gene mutation and metabolic engineering could promote lincomycin biosynthesis and might be helpful for reducing the production of other industrially unnecessary byproduct.